A fast multipole algorithm for radiative heat transfer in 3D semitransparent media. (December 2018) - Han, Yaochuang; Nie, Yufeng; Dong, Hao
Abstract: This paper presents a fast multipole accelerated boundary element method for simulating the radiative heat transfer in 3D semitransparent media. The participating media is absorbing, emitting and isotropically scattering. The proposed implementation adopts the boundary element method based on the collocation scheme to discretize the radiative integral transfer equations. The resulting algebraic system is solved iteratively with GMRES (generalised minimum residual method). A kernel-independent fast multipole method to accelerate the matrix-vector product in each iteration. It is found from three numerical examples that the computational efficiency of the developed fast algorithm is much better than the conventional boundary element method.